Assessment of residual pesticides and other organic pollutants using passive samplers in Can Tho River, Vietnam, and Cagayan de Oro River Basin, Philippines - Salingay, Maria Luisa Baiño; Zevenbergen, Chris; Pathirana, Assela (Frontiers in Water, 2024)
Agriculture-dependent developing Southeast Asian countries need to assess residual pesticides in receiving water from agricultural runoff as one of the basis for the establishment of baseline data. Monitoring residual pesticides in surface water is challenging due to pesticides’ irregular/intermittent emission and low solubility in water. To address the challenge of pesticide assessment, passive samplers composed of silicon rubber sheets (SR) and speedisk (SD) were used to capture hydrophobic and hydrophilic organic pesticides and other organic pollutants, respectively. Samplers were submerged uninterruptedly for at least 30 days in three selected sites in Can Tho River, Mekong Delta, Vietnam, and Cagayan de Oro River Basin, Philippines, for 2 years. Passive samplers (SR spiked with 232 pesticides) captured 83 and 69 residual pesticides at concentrations of ng/L levels in Vietnam and the Philippines, respectively, which is unattainable through conventional grab sampling methods. Trace concentrations of banned compounds such as OCPs, PCBs, and PAHs were also detected at pg./L levels. The success of this alternative methodology can be attributed to the combination of passive samplers tailored for nonpolar (water-insoluble) and polar (water-soluble) organic contaminants coupled with sensitive analytical instruments, including GCMSMS and LCMSMS.